Research Trends on Ethnoscience in Physics Learning (EPL): A Bibliometric Network Analysis - Titin Sunarti; Nadi Suprapto; Suliyanah; Muhammad Satriawan; Hasan Nuurul Hidaayatullaah (Indonesia Approach Education, 2024)
In this modern era of education, understanding EPL research trends plays an important role in the development of innovative physics education. The general aim of this research is to comprehensively explore the landscape of Ethnoscience in Physics Learning (EPL). This study used bibliometric analysis to evaluate publications. Data was collected from Scopus and analyzed using VOSviewer and Biblioshiny-Bibliometrix software. The publication trend of EPL research varies annually, with significant growth since 2000 and the highest peak in 2021. Articles are the dominant document type in EPL research, with the average total citations per article varying significantly from year to year. Journal of Physics: Conference Series is the top source for EPL research. The main affiliations and countries contributing significantly are Semarang State University and Indonesia, while physics and astronomy dominate as the main subjects. The authors who contributed and had the most citations in EPL-related research were Beggs J. M. & Plenz D. The keywords that dominated and became a new trend were Physics, Cell Culture, Article, Human, and Student. The novelty of this study lies in its bibliometric approach and network analysis that provides deep insights into research trends and relationships within the field of ethnoscience in physics learning, contributing to a better understanding of the development of physics education.